Dangerous pilgrimages transatlantic mythologies and the novel - Bradbury, Malcolm 1932-2000 (Viking Penguin, 1996)
Malcolm Bradbury, who has been writing about various aspects of American and British literature for more than three decades, tracks this long-lived relationship and the accompanying myths with expert zest and enthusiasm. It is an exhilarating journey - from Chateaubriand's primeval America, crisscrossing the Atlantic to Henry James (who invented Paris) and Edith Wharton's focus on the American in Europe, to the European tours of America in the tradition of Evelyn Waugh (who invented postmodern L.A.) and Malcolm Lowry, to the contemporary "frequent flyer" novelists for whom both continents represents a kind of hyper-reality